2012
DOI: 10.1186/1465-9921-13-77
|View full text |Cite
|
Sign up to set email alerts
|

Low tidal volume protects pulmonary vasomotor function from “second-hit” injury in acute lung injury rats

Abstract: BackgroundSepsis could induce indirect acute lung injury(ALI), and pulmonary vasomotor dysfunction. While low tidal volume is advocated for treatment of ALI patients. However, there is no evidence for low tidal volume that it could mitigate pulmonary vasomotor dysfunction in indirect ALI. Our study is to evaluate whether low tidal volume ventilation could protect the pulmonary vascular function in indirect lipopolysaccharide (LPS) induced acute lung injury rats.MethodsAn indirect ALI rat model was induced by i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 29 publications
3
18
0
Order By: Relevance
“…Previous studies reported that levels of circulatory and pulmonary ET-1 are elevated in ARDS models [16,21,22]. The current data are consistent with data from these earlier reports.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Previous studies reported that levels of circulatory and pulmonary ET-1 are elevated in ARDS models [16,21,22]. The current data are consistent with data from these earlier reports.…”
Section: Discussionsupporting
confidence: 92%
“…Thus, collectively, data from the present study and these earlier studies show a significant alteration in levels of both circulatory and pulmonary ET-1 compared to the healthy control subjects in lavage-induced surfactant depleted ARDS models. Secondly, these data suggest validation of the present animal model as a suitable model for ARDS, including the patterns of circulatory and pulmonary ET-1 levels as seen in other frequently used ARDS models [16,21,22].…”
Section: Discussionmentioning
confidence: 77%
“…Both iNOS and endothelin-1 have been associated with astrocyte dysfunction in several neurological conditions, including brain ischemia [19,20]. A recent study in rats further con rmed the association between tidal volume, endothelin-1 and NO synthetase [21]. Thus, one hypothesis to account for our results could be formulated as follows: low tidal volume ventilation, perhaps coupled with the effects of a higher respiratory rate, leads to increased endothelin levels and induced NO synthetase.…”
Section: Discussionsupporting
confidence: 67%
“…Zhang et al (2010) reported that pulmonary arteries of LPStreated rats have an increase in the contractile response to PE. In addition, LPS-treated rabbits showed a decrease in both endothelium-dependent and -independent vasorelaxation (Huang et al 2005).Conversely, the relaxation response to SNP in PA rings of LPS-treated rats has been shown to be unaffected (Pan et al 2012). In this study, LPS-treated rats showed an increase in the contractile response of PA rings to PE without affecting either endothelium-dependent or -independent vasorelaxation.…”
Section: Activation Of Nf-κb Is Increased During Inflammation and It mentioning
confidence: 94%